The Effect of Listening to English Classical Music and Murottal on Reducing Depression Levels in the Elderly in Bangun Rejo Village, Tanjung Morawa Regency in 2024 - Batubara, Zulkarnain; Surbakti, Imran; Rosmega, Rosmega (Institute of Computer Science (IOCS), 2024)
Depression is the most common psychological disorder in the last years of a person's life. Depression in the elderly has several impacts, including shortening life expectancy by worsening physical decline in the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024, inhibiting the fulfillment of developmental tasks in the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024, reducing the quality of life of the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024, draining the emotions and finances of those affected as well as their families and social support systems. The physioListening program given to the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024 who experience depression is listening to English Classical Music and murottal. Research Objectives: This study aims to determine the effect of Listening to English Classical Music and Murottal on reducing depression levels in the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024. Research Methods: This research method uses a quasi-experimental design with a pre and post test with control group design. The number of samples used was 12 people. Research Results: Statistical tests using the Wilcoxon test showed that there was an effect of listening to English Classical Music and Murottal music on reducing depression levels in the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024. with a p value = 0.041 (<0.05). Meanwhile, for the difference in influence test, the p value was obtained = 0.036 (<0.05). Conclusion: With these results, it can be concluded that there is an effect of listening to English Classical Music and Murottal music on reducing depression levels in the elderly in Bangun Rejo Village, Tanjung Morawa District in 2024.